EVALUASI SISTEM PENCATATAN DAN PELAPORAN DESA SIAGA DI WILAYAH PUSKESMAS SUMOWONO KECAMATAN SUMOWONO KABUPATEN SEMARANG - Yudhy Dharmawan (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2015)
ABSTRACTThere are 16 infant mortality in Puskesmas Sumowono, which could be prevented by surveillance MCH, which is activities in Desa Siaga. Desa Siaga in Puskesmas Sumowono commonly inactive. One possible cause is the ineffectiveness of a system for recording and reporting Alert Village. Design research using data collection techniques interviews and observations, the research time for 5 months, with a purposive sampling technique, and a qualitative analysis using the analytical framework of the Human Resources, Organization and Technology. The results of the study of the Human, it can be concluded that the understanding of the recording and reporting officer Desa Siaga is still unfavorable, because of its use are rare, and the lack of specific reporting formats Desa Siaga. The village midwife was not satisfied due to repeated recording, so there are double burden of recording. In Organization side, that is needed to support the operations and recording reporting of the Desa Siaga. In terms of reporting technology is simple with no special formatting, still have a duplication of data recording and reporting MCH. Recording results reporting information is only used for stratification purposes of Desa Siaga. It is recommended to use information technology in order to ensure the validity of the data and avoid duplication of data.Key word :Recording Reporting, Desa Siaga Kesmasindo, Volume 7( 2), Januari 2015, Hal. 88-105